(untitled) (Bangladesh Journal of Child Health, 2010)
Objectives: To evaluate the clinico-demographic profile and management of foreign body (FB) aspiration in hospitalized patients. Methodology: This was a retrospective study conducted at the National Institute of Diseases of the Chest and Heart (NIDCH), Dhaka during the period of October 1994 to February 2006. Medical records were used for collection of cases. The diagnosis of FB aspiration was made from documented presenting features, physical findings, investigations of chest radiology, CT scan whenever done and management outcome with rigid bronchoscopy and surgical interventions like bronchotomy or resection surgery. Results: Most of the patients 374 (97.5%) were children up to 15 years of age with the peak age of 1-10 years (81.3%). Males were affected more (63%) than females (37%). The majority of the patients (96%) were from poor socio-economic status. Most of the patients 297 (77.7%) presented early (within 7 days of aspiration) with cough and respiratory distress. There was late (after 7 days up to 12 years) presentation in 85 (22.2%) cases with respiratory complications. FB was found to be radio-opaque in 122 (31.9%) cases on chest imaging. Rigid bronchoscopy was attempted in all cases initially and it was successful to remove FB in 99.6% cases in patients who presented early. But it failed to remove the FB in 49 (57.6%) of cases when the patients presented late. Most of the FBs were of natural in origin 247 (64.6%) and the number of artificial FBs was less 135 (35.3%). FBs found impacted more on the right bronchial tree in 230 (60.2%), followed by left side in 121 (31.6%) and central airway in 31 (8.1%) cases. In failed cases, bronchotomy, lobectomy and pneumonectomy were the other modalities (57.6%) of management. Conclusion: Children of the age group 1-10 years were found most vulnerable for FB aspiration. FB of natural origin were common in our situation. FBs were impacted mostly on the right side. Removal of FB by rigid bronchoscopy was excellent when the patients presented early. Other difficult modalities of management like bronchotomy, lobectomy and pneumonectomy were needed in cases of late presentation. DOI: 10.3329/bjch.v30i1.6177 Bangladesh J Child Health 2006; VOL 30 (1/2/3): 12-16